تثمين وتوصيف المواد المستخلصة من النباتات الطبية والعطرية - خليل حنين; بن سديرة أسماء (جامعة الشهيد حمه لخضر الوادي, 2024)
تعتبر النباتات الطبية موردا هاما للمركبات الكيميائية المتنوعة، لهذا تم ابتكار طرق متعددة لاستخلاص هذه المركبات، من أهم هذه المستخلصات الزيوت العطرية، تتكون هذه الأخيرة من العديد من المكونات؛ هذه الد ا رسة تهدف لإيجاد نموذج رياضي لتصنيف الزيوت العطرية بواسطة التحليل الكيمومتري، شملت الد ا رسة 53 نبات من 71 عائلة مختلفة ذات استعمالات طبية، تمت عملية استخلاصها بطريقة النقع الساخن )طريقة الزيت الحامل(، ثم تحليل هذه الزيوت العطرية المستخلصة بواسطة كروماتوغ ا رفيا غاز-كتلة للكشف عن مكوناتها، تم إد ا رج بيانات الكروماتوغ ا رم المتحصل وذلك باستخدام برنامج )HCA( و تحليل العنقود الهرمي ،)PCA( عليها في مصفوفة وتحليلها بطريقة المكون الرئيسي ؛SIMCA باستخدام برنامج ال )PLS-DA( وطريقة تحليل المربعات الجزئية الصغرى ،)Orang data mining) أورنج ،PLS-DA على أساس التشابه في التركيب الكيميائي، لكن نتائج ال HCA و تصنيف ال PCA كانت نتائج تصنيف ال F-، Q=0.0192، R2 Adjs=249.0،R2= كانت ممتازة للحصول على نموذج تنبؤ معامل انحداره: 0.941 كما أنه يعد كافيا للتمييز بين محتوى التربينات والمركبات ،RMSECV= و 0.16 ، P-value=0.015 ،test=0.043 الأكسيجينية للزيوت العطرية. Medicinal plants are an important source of diverse chemical compounds. Therefore, various methods have been developed to extract these compounds. Among the most important extracts are essential oils, which consist of many components. This study aims to develop a mathematical model for classifying essential oils using chemometric analysis. The study included 35 plants from 17 different families with medicinal uses. The extraction process was carried out using the hot soaking method (carrier oil method), and the extracted essential oils were analyzed by gas chromatography-mass spectrometry (GC-MS) to identify their components. The obtained chromatogram data were inserted into a matrix and analyzed using Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) using Orange data mining software, and Partial Least Squares Discriminant Analysis (PLS-DA) using SIMCA software. The PCA and HCA classification results were based on the similarity in chemical composition. However, the PLS-DA results were excellent, obtaining a predictive model with regression coefficients: R2=0.941, R2 Adjusted=0.942, Q=0.0192, F-test=0.043, P-value=0.015, and RMSECV=0.16. It is also sufficient to distinguish between the terpene and oxygenated compound content of the essential oils.
مذكرات ماستر تخصص هندسة كيميائية
Keywords: النباتات الطبية، الزيوت العطرية، نموذج رياضي، تصنيف كيم ومتري، الكروماتوغ ا رفيا كتلة-غاز; Medicinal plants; essential oils; mathematical model; chemometric classification; gas chromatography-mass spectrometry (GC-MS).